Piperine Alters the Pharmacokinetics and Anticoagulation of Warfarin in Rats - Zayed A; Babaresh WM; Darweesh RS; El-Elimat T; Hawamdeh SS (Dove Medical Press, 2020)
Aref Zayed,1 Wahby M Babaresh,1 Ruba S Darweesh,2 Tamam El-Elimat,1 Sahar S Hawamdeh1 1Department of Medicinal Chemistry and Pharmacognosy, Faculty of Pharmacy, Jordan University of Science and Technology, Irbid 22110, Jordan; 2Department of Pharmaceutical Technology, Faculty of Pharmacy, Jordan University of Science and Technology, Irbid 22110, JordanCorrespondence: Aref Zayed Tel +962 2 7201000, Ext. 23240Fax +962 2 7201075Email alzayed@just.edu.joIntroduction: Piperine, the bioactive compound of black pepper, and warfarin are metabolized by cytochrome P450 enzymes and are both highly plasma protein-bound compounds. In this study, we evaluated the effect of co-administered piperine on the pharmacokinetics and anticoagulation of warfarin in rats.Methods: We studied four Sprague-Dawley rat groups: a negative control group receiving only oral warfarin, a test group receiving warfarin plus piperine, a positive control group receiving warfarin plus sulfaphenazole (CYP2C inhibitor), and another positive control group receiving warfarin plus ketoconazole (CYP3A inhibitor). We also analyzed plasma concentrations of warfarin and its major metabolite, 7-hydoxywarfarin. Blood clotting time, calculated as international normalized ratio (INR), was also measured.Results: Our results showed that although co-administration of piperine produced a non-significant decrease in warfarin concentrations, it resulted in significantly lower 7-hydroxywarfarin metabolite concentrations. Piperine significantly decreased, by sixfold, AUC0–∞, by eightfold, Cmax, but significantly increased, by fivefold, CL/F and, by sixfold, Vd/F of 7-hydroxywarfarin. The INR values were consistent with the decrease in warfarin concentration in the presence of piperine and showed a significant decrease at 24 h after warfarin dose.Conclusion: We conclude that piperine could be a potent inhibitor of cytochrome P450 metabolism of warfarin in vivo and, contrary to the expectation, may reduce the plasma concentration and anticoagulation of warfarin. This interaction could have a clinical significance and should be investigated in patients.Keywords: warfarin, 7-hydroxywarfarin, piperine, pharmacokinetics, herb–drug interaction, black pepper